Formation of structure in molecular clouds: A case study - Heitsch, F; Burkert, A; Hartmann, L; Slyz, A; Devriendt, J (Institute of Physics Publishing, 2005)
Molecular clouds (MCs) are highly structured and turbulent. Colliding gas streams of atomic hydrogen have been suggested as a possible source of MCs, imprinting the filamentary structure as a consequence of dynamical and thermal instabilities. We present a two-dimensional numerical analysis of MC formation via converging H I flows. Even with modest flow speeds and completely uniform inflows, nonlinear density perturbations arise as possible precursors of MCs. Thus, we suggest that MCs are inevitably formed with substantial structure, e.g., strong density and velocity fluctuations, which provide the initial conditions for subsequent gravitational collapse and star formation in a variety of Galactic and extragalactic environments. © 2005. The American Astronomical Society. All rights reserved.